2004
DOI: 10.1089/0897715041269623
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury Elevates Glycogen and Induces Tolerance to Ischemia in Rat Brain

Abstract: Previous studies have demonstrated that traumatic brain injury (TBI) increases the vulnerability of the brain to an acute episode of hypoxia-ischemia. The objective of the present study was to determine whether TBI alters the vulnerability of the brain to a delayed episode of ischemia and, if so, to identify contributing mechanisms. Sprague-Dawley rats were subjected to lateral fluid-percussion (FP) brain injury (n = 14) of moderate severity (2.3-2.5 atm), or sham-injury (n = 12). After recovery for 24 h, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…This inactivity prevents effector binding downstream signaling (i.e., glycogen ca- tabolism, etc.). In TBI, glycogen levels are increased compared with control, supporting the downstream effects impaired by GDI (Otori et al, 2004).…”
Section: Identification Of Nitrated Proteins In Gcee-treated Tbi Ratsmentioning
confidence: 74%
“…This inactivity prevents effector binding downstream signaling (i.e., glycogen ca- tabolism, etc.). In TBI, glycogen levels are increased compared with control, supporting the downstream effects impaired by GDI (Otori et al, 2004).…”
Section: Identification Of Nitrated Proteins In Gcee-treated Tbi Ratsmentioning
confidence: 74%
“…Lastly, PPC flux was determined relative to glycolytic activity, not necessarily accounting for all the excess glucose that was consumed by nonoxidative pathways in the brain, such as glycogen synthesis. Other studies have suggested that these fluxes may be increased after injury as well (Otori et al, 2004). …”
Section: Limitationsmentioning
confidence: 94%
“…While it is rational to assume that TBI increases the brain's vulnerability to secondary injury, preconditioning effects have been demonstrated (Otori et al, 2004). Fluid percussion (FP) injury given 1 hr prior to ischemia exaccerbates hippocampal cell loss (Jenkins et al, 1989), but when given 24hr before ischemia it is neuroprotective (Otori et al, 2004).…”
Section: Introductionmentioning
confidence: 99%